Occupational Characteristics of Leading Canadian Executives - Moore, Larry; Daly, William (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1973)
The purpose of this study is to investigate the geographic origins, the social and educational backgrounds and the occupational and career patterns of top executives in Canadian Companies.